Impact of Comorbidities and Frailty on Early Shunt Failure in Geriatric Patients With Normal Pressure Hydrocephalus - Hadjiathanasiou, Alexis; Kilinc, Fatma; Behmanesh, Bedjan; Bernstock, Joshua; Güresir, Erdem; Heimann, Muriel; Konczalla, Jürgen; Scharnböck, Elisa; Schneider, Matthias; Weinhold, Leonie; Seifert, Volker; Vatter, Hartmut; et al. (Frontiers in Medicine, 2020)
Background/Aim: Older patients are considered to bear a higher perioperative risk. Since idiopathic normal pressure hydrocephalus (NPH) predominantly concerns older patients, identifying risk factors for early shunt failure for preoperative risk/benefit assessment is indispensable for indication and/or consultation of patients for ventriculoperitoneal shunting (VPS). Methods: We performed a retrospective study design, including data acquired from two university hospital neurosurgical institutions between 2012 and 2019. Overall, 211 consecutive patients with clinical/radiological signs for NPH who additionally showed alleviation of symptoms after lumbar cerebrospinal fluid (CSF) drainage, received VPS and were included for further analysis. Frailty was measured using the Clinical Frailty Scale (CFS). Main outcome was early shunt failure or postoperative complications within 30 days after initial VPS surgery. Results: The overall complication rate was 14%. Patient-related complications were observed in 13 patients (6%) and procedure-related complications in 16 patients (8%). Early postoperative complications resulted in a significantly prolonged length of hospital stay 6.9 ± 6.8 vs. 10.8 ± 11.8 days (p=0.03). Diabetes mellitus with end-organ damage (OR 35.4, 95% CI 6.6-189.4, p<0.0001) as well as preexisting Parkinson’s disease were associated with early patient-related postsurgical complications after VPS for NPH. Conclusions: Patients comorbidities but not frailty were associated with early postoperative patient-related complications in patients suffering NPH. While frailty may deter patients from other (neurosurgical) procedures, VPS surgery might contribute to treating NPH in these patients at a tolerable risk.